SAffold viruses in pediatric patients with diarrhea in Thailand - Yodmeeklin,A. (Wiley-Liss Inc., 2015)
© 2015 Wiley Periodicals, Inc. Saffold virus (SAFV) is a newly discovered human virus which is classified into the genus Cardiovirus of the family Picornaviridae. A total of 608 fecal specimens collected during January 2012 to December 2013 from children with diarrhea in Chiang Mai, Thailand were investigated for SAFV by RT-nested PCR and sequence analysis. Of these, nine out of 608 (1.5%) were positive for SAFVs and four genotypes were identified, SAFV1, SAFV2, SAFV3, and SAFV4. SAFV mono-infection was found in five cases (CMH-S038-12, CMH-S071-12, CMH-S102-12, CMH-N029-12, and CMH-S048-13), while co-infection with other viruses causing diarrhea was observed in four cases (CMH-S021-12, CMH-S115-12, CMH-N048-13 and CMH-N103-13). This study provides more information about the genetic background of SAFV circulating in pediatric patients with diarrhea in Thailand.